Evolution of the selfing syndrome in Ipomoea - Duncan, Tanya M.; Rausher, Mark D. (Frontiers in Plant Science, 2013)
Plants that are highly selfing typically exhibit a suite of morphological traits termed a “selfing syndrome”, including reduced corollas and reproductive structures, loss of corolla pigmentation, little anther-stigma separation, and a lower pollen/ovule (P/O) ratio. While it is typically assumed that these changes are adaptive, few attempts have been made to determine whether they result from the operation of natural selection or genetic drift. In the southeastern United States, Ipomoea lacunosa has evolved a typical selfing syndrome compared to its close relative, I. cordatotriloba. Microsatellite markers confirmed that selfing rates are substantially higher in I. lacunosa. Furthermore, using a standard QST – FST comparison, we evaluated the relative importance of selection and drift in the evolution of selfing syndrome traits in I. lacunosa. The analysis demonstrated that natural selection is responsible for the evolution of reduced corolla size, anther-stigma distance, and stigma length in this species. By contrast, leaf characteristics unrelated to selfing were found to have diverged largely by genetic drift. Our study provides one of the first confirmations that natural selection drives the evolution of selfing-syndrome traits.